Barry M. Mitnick (ed.), Corporate Political Agency: The Construction of Competition in Public Affairs, Newsbury Park, CA: Sage Publications, 1993, 327 s., £ 19,50. - Sonne Nørgaard, Asbjørn (Politica, 1994)
-